Pengaruh Kombinasi Dosis Pupuk Organik Cair dan Pupuk NPK Majemuk Terhadap Pertumbuhan dan Hasil Tanaman Selada Keriting (Lactuca sativa L.) Varietas Grand Rapids Pada Sistem Vertikultur - Redi Ramadhan; Bastaman Syah; Darso Sugiono (Jurnal Ilmiah Wahana Pendidikan, 2021)
The research was carried out in Kp. Ciheuleut, Cimulang Village, Kec. Rancabungur, Kab. Bogor from June to August 2021. The research method used is an experimental method with a single factor Randomized Block Design (RDB) with 7 treatments, namely: A (Without POC Nasa and NPK), B (POC Nasa 150 ml/plant), C (POC Nasa 125 ml/plant + NPK 1 g/plant), D (POC Nasa 100 ml/plant + NPK 2 g/plant), E (POC Nasa 75 ml/plant + NPK 3 g/plant), F (POC Nasa 50 ml/plant + NPK 4 g/plant, and G (NPK 5 g/plant). Each treatment was repeated 4 times, resulting in 28 experimental units. The results showed that there was a significant effect of the combination treatment of liquid organic fertilizer doses and compound NPK fertilizer on plant height at 35 DAP, number of leaves at 28 DAP and 35 DAP, leaf area, root fresh weight, and fresh weight of curly lettuce (Lactuca sativa L.) Grand Rapids variety in a verticulture system. Treatment E, which was a combination dose of POC Nasa 75 ml/plant + NPK 3 g/plant, gave the highest yield for plant height 35 days after planting at 24.35 cm, plant leaves at 28 and 35 days after planting at 10.70 strands and 14.70 strands, plant leaf area of ​​532.71 cm2, the fresh weight roots of 16.18 grams, and fresh weight plants of 173,70 grams.